Abstract 1122‐000227: Stenting Versus Medical Treatment for Chronic Internal Carotid Artery Occlusions: A Systematic Review and Meta‐analysis - Cynthia Zevallos Mau; Cynthia B Zevallos; Milagros Galecio‐Castillo; Sameer Ansari; Julie Weng; Juan Vivanco‐Suarez; Andres Dajles; Darko Quispe‐Orozco; Alan Mendez‐Ruiz; Mudassir Farooqui; Santiago Ortega‐Gutierrez (Stroke: Vascular and Interventional Neurology, 2021)
Introduction: Chronic internal carotid occlusion is responsible for 10–15% ischemic strokes or transit ischemic attacks (TIA). Subsequent ipsilateral ischemic stroke rate is 5.9% per year. However, this risk can increase up to 23% in two years in a subgroup of patients with poor collaterals regardless of medical therapy with antiplatelet or anticoagulant agents. Prevention of subsequent stroke in patients with carotid artery occlusion remains a difficult challenge. Carotid artery stenting (CAS) has recently been considered in its management. However, there is ambiguity on its safety. We aim to evaluate the safety and feasibility of CAS and compared it with medical management. Methods: We performed a systematic review and meta‐analysis to compare long‐term outcome (stroke recurrence) of current carotid occlusion treatments (CAS vs medical therapy). Two independent reviewers performed the screening, data extraction, and quality assessment. A random effects model was used for analysis. Results: A total of 5720 studies were screened. Of these, 11 studies were included in our systematic review and meta‐analysis of proportions. The CAS group has lower proportions of recurrent strokes (5% vs 30%,) after 30 days than medical therapy alone. Additionally, the proportion of periprocedural intracranial hemorrhage was 4.4% (95% CI 2.5 to 6.8) in the CAS group. Conclusions: CAS of the chronically occluded cervical ICA seems to be a safe procedure with lower rates of recurrent stroke in clinical follow up. Future randomized studies are warranted to guide the optimal management of this complex disease.